2021
DOI: 10.1038/s41467-021-24342-y
|View full text |Cite
|
Sign up to set email alerts
|

The antiandrogen enzalutamide downregulates TMPRSS2 and reduces cellular entry of SARS-CoV-2 in human lung cells

Abstract: SARS-CoV-2 attacks various organs, most destructively the lung, and cellular entry requires two host cell surface proteins: ACE2 and TMPRSS2. Downregulation of one or both of these is thus a potential therapeutic approach for COVID-19. TMPRSS2 is a known target of the androgen receptor, a ligand-activated transcription factor; androgen receptor activation increases TMPRSS2 levels in various tissues, most notably prostate. We show here that treatment with the antiandrogen enzalutamide—a well-tolerated drug wide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 83 publications
2
82
0
Order By: Relevance
“…While a reduction in the efficacy of proxalutamide could be expected due to the P.1 variant's typical resistance to usual care for COVID-19, since all the three major aspects of the P.1 variant (high dependence on TMPRSS2 for cell entry, dysfunctional exacerbated inflammatory and immunologic reactions, and severe endothelial dysfunction) seem to be specially targeted by an anti-androgen [ 41 , 42 ], the high efficacy of proxalutamide in the P.1 variant could also be justified by these peculiarities of the variant present in the RCTs. However, enzalutamide, a high-potent drug from the same drug class as proxalutamide although with weaker antiandrogen activity, demonstrated to dramatically reduce SARS-CoV-2 cell entry in the lung by downregulating TMPRS22, in a non-P.1 SARS-CoV-2 variant [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a reduction in the efficacy of proxalutamide could be expected due to the P.1 variant's typical resistance to usual care for COVID-19, since all the three major aspects of the P.1 variant (high dependence on TMPRSS2 for cell entry, dysfunctional exacerbated inflammatory and immunologic reactions, and severe endothelial dysfunction) seem to be specially targeted by an anti-androgen [ 41 , 42 ], the high efficacy of proxalutamide in the P.1 variant could also be justified by these peculiarities of the variant present in the RCTs. However, enzalutamide, a high-potent drug from the same drug class as proxalutamide although with weaker antiandrogen activity, demonstrated to dramatically reduce SARS-CoV-2 cell entry in the lung by downregulating TMPRS22, in a non-P.1 SARS-CoV-2 variant [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of androgens on COVID-19 is well established from multiple epidemiological observations [ 1 - 17 , 22 ], clinical studies [ 23 - 33 ], and strong and definitive biological plausibility [ 18 - 20 , 40 - 43 ]. Even ADT for castration-resistant prostate cancer, which has been found to independently increase the risk of global mortality in case of any secondary illness, when compared to men not under ADT [ 56 ], demonstrated not only to have an exception when the disease is COVID-19, but also to provide relative protection from severe COVID-19 and death [ 14 - 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a Brazilian study tested the antiandrogen proxalutamide in nonhospitalized patients [17] and found that inhibition of androgen signaling appeared to affect viral internalization. Several experimental studies support a role of androgen inhibition in SARS-CoV-2 virulence [4] , [18] , although contrasting data also exist [19] . The mechanism may be context-dependent, since different species, cell lines, cell types, and model systems generate variable results.…”
Section: Discussionmentioning
confidence: 99%
“…One of these, TMPRSS2, modulates viral spike proteins that enable SARS-CoV-2 internalization. In prostate cancer cells, the androgen receptor (AR) directly regulates TMPRSS2, and this mechanism has also been described in lung cells from both men and women [3] , [4] , [5] . Androgens may also regulate ACE2, another critical protein for virus internalization [3] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the androgen-induced TMPRSS2 regulation in lung epithelial cells, some previous data showed no effects of Enza on pulmonary TMPRSS2 27 . However, several studies have demonstrated that androgen regulates the expression of TMPRSS2 in subsets of lung epithelial cells, while treatment with Enza reduces TMPRSS2 levels in human lung cells 28 , thus inhibiting SARS-CoV-2 infections in vitro 29 . As compared to the numerous investigations of AR-mediated TMRPSS2 expression in the lungs, there are few reports of this regulation in other organs, such as the small intestine and kidneys 30 .…”
Section: Discussionmentioning
confidence: 99%